مساهمة برنامج التجديد الفلاحي والريفي في إنتاج التمور بولاية أدرار - بلال، بوجمعة (جامعة 20 اوت 1955 سكيكدة, 2018)
تهدف هذه الورقة البحثية إلى دراسة برنامج التجديد الفلاحي والريفي باعتباره رؤية جديدة للسلطات المحلية بولاية أدرار لإنعاش القطاع الفلاحي، وكذا انعكاسه على أداء إنتاج التمور. وخلصت الدراسة إلى أن التطور الإيجابي في إنتاج التمور خلال الفترة (2010- 2016)، يمكن إرجاعه إلى الجهود المبذولة من قبل الدولة لاستصلاح الأراضي، بالإضافة إلى زيادة عدد المستثمرات الجديدة بولاية أدرار.
This paper deals aims to shed light on the agricultural and rural renewal program as a new vision to the local authorities in the wilaya of Adrar for the recovery of the agricultural sector, as well as the impacts on the performance of the dates production. The study found that the positive development of dates production for the period (2010–2016), due to the efforts of the state for land reclamation, and Development of the number of new investors in the wilaya of adrar.
Keywords: استصلاح الأراضى -- الانتاج الزراعى -- ولاية أدرار -- الجزائر